Cantos de bar: sociabilidades e boemia na cidade de Natal - Freitas, Viltany Oliveira (2013)
The academic work Bar Corners: sociability and bohemia in the Natal City (1946-1960) has as objective the study of a representation of the literary bohemia in Natal in the second half of the 1940 s and 50 s, by means of analyses of the memory books and the chronicles of the newspapers A Ordem and A República. In order to have a better understanding concerning the subject, in the first chapter we try to show the transformations which have occurred in Natal and, consequently, within Natal sociability during the first half of the twentieth century. The bohemia, demonstrated in this dissertation as a way of sociability, expressed itself through the meetings in bars and the serenades. In the second chapter, the study conducted a mapping of the bohemian spaces (cafes, candy stores, bars and prostituition houses) and established the differences between these spaces. We ideated the spaces as the stage of interpersonal relations, as people went to these places in the attempt to participate of the conversation groups that were found there, choosing them according to their affinity and personal interests. The last chapter has the purpose of investigating the bohemia in Natal through the experience of the chronicler Newton Navarro, who used to roam the dark streets of Ribeira in search for open bars, extending bohemia until dawn. The intellectual activity was associated with his bohemian practices. As he frequented the marginal areas in Natal, Navarro wrote about them in the major newspapers of the city